2023
DOI: 10.3389/fpsyg.2023.1136141
|View full text |Cite
|
Sign up to set email alerts
|

Gender-moderated effects of academic self-concept on achievement, motivation, performance, and self-efficacy: A systematic review

Abstract: Although academic self-concept plays a crucial role in promoting students' education, there is a paucity of studies simultaneously exploring the gender-moderated effects of academic self-concept. This study aimed to explore gender-moderated effects of academic self-concept on achievement, motivation, performance, and self-efficacy. With Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol (PRISMA-P) and STARLITE criteria, this study screened and assessed the retrieved literature, finally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…We also found that female officers rated the live CIC task would be significantly more "difficult" and "stressful" than male officers, which may be attributed to sex differences in self-efficacy. In general, Scandinavian women report lower self-efficacy than men (Bonsaksen et al, 2019), a result often found in educational research (Wang & Yu, 2023). As officers were graduate-level students at the PUC, reduced selfefficacy and confidence in one's abilities among women in educational contexts may account for the higher ratings of anticipated difficulty and stress.…”
Section: -Sex-based Differences In Physiological and Psychological St...mentioning
confidence: 96%
“…We also found that female officers rated the live CIC task would be significantly more "difficult" and "stressful" than male officers, which may be attributed to sex differences in self-efficacy. In general, Scandinavian women report lower self-efficacy than men (Bonsaksen et al, 2019), a result often found in educational research (Wang & Yu, 2023). As officers were graduate-level students at the PUC, reduced selfefficacy and confidence in one's abilities among women in educational contexts may account for the higher ratings of anticipated difficulty and stress.…”
Section: -Sex-based Differences In Physiological and Psychological St...mentioning
confidence: 96%
“…For example, males and females vary in how they perceive peer acceptance, as boys show a greater inaccuracy for perceived acceptance by same-sex peers compared to girls, while girls seem to have a more negatively biased perception of opposite-sex acceptance compared to boys [52]. In a recent systematic review [53], it was found that gender moderated the effects of actual social status on scholastic achievement, with adolescent females being more affected by poor acceptance. Further, Bédard et al [37] found that girls may show vulnerability to peer acceptance at an earlier age than boys.…”
Section: Gender Differencesmentioning
confidence: 99%
“…The findings of Bosch and Wilbert (2023) reveal that task interest had a robust relationship with the individual's self-evaluation processes. Even in academics, Gorges et al (2018) pointed out that performance was a crucial variable in academic self-concept research and positively associated with performance (Wang and Yu, 2023;Guo et al, 2020;Colmar et al, 2019). Celebre (2022) found that when employees (teachers) perceived themselves positively with high selfefficacy and motivation and overall high self-concept, the perceived self-concept is supported by the best practices in their assessment.…”
Section: Development Of the Hypothesesmentioning
confidence: 99%